Co-infection dynamics of B. afzelii and TBEV in C3H mice: insights and implications for future research - Porcelli, Stefania; Heckmann, Aurélie; Deshuillers, Pierre Lucien; Wu-Chuang, Alejandra; Galon, Cleménce; Mateos-Hernandez, Lourdes; Rakotobe, Sabine; Canini, Laetitia; Rego, Ryan O M; Simo, Ladislav; Lagrée, Anne-Claire; Cabezas-Cruz, Alejandro; et al. (Infection and immunity, 2024)
Ticks are important vectors of disease, particularly in the context of One Health, where tick-borne diseases (TBDs) are increasingly prevalent worldwide. TBDs often involve co-infections, where multiple pathogens co-exist in a single host. Patients with chronic Lyme disease often have co-infections with other bacteria or parasites. This study aimed to create a co-infection model with Borrelia afzelii and tick-borne encephalitis virus (TBEV) in C3H mice and to evaluate symptoms, mortality, and pathogen level compared to single infections. Successful co-infection of C3H mice with B. afzelii and TBEV was achieved. Outcomes varied, depending on the timing of infection. When TBEV infection followed B. afzelii infection by 9 days, TBEV symptoms worsened and virus levels increased. Conversely, mice infected 21 days apart with TBEV showed milder symptoms and lower mortality. Simultaneous infection resulted in mild symptoms and no deaths. However, our model did not effectively infect ticks with TBEV, possibly due to suboptimal dosing, highlighting the challenges of replicating natural conditions. Understanding the consequences of co-infection is crucial, given the increasing prevalence of TBD. Co-infected individuals may experience exacerbated symptoms, highlighting the need for a comprehensive understanding through refined animal models. This study advances knowledge of TBD and highlights the importance of exploring co-infection dynamics in host-pathogen interactions.
Keywords: Encephalitis Viruses, Tick-Borne; Encephalitis, Tick-Borne; koinfekce; klíšťová encefalitida; Borrelia burgdorferi Group; Coinfection; viry klíšťové encefalitidy; Lyme Disease; lymeská nemoc; Female; myši inbrední C3H; Mice, Inbred C3H; zvířata; myši; Mice; C3H mice; co-infection; tick-borne pathogens; ženské pohlaví; Borrelia burgdorferi komplex; pathogen fitness; Animals; pathogen invasiveness; Disease Models, Animal; modely nemocí na zvířatech